TEACHERS’ AND STUDENTS’ PERCEPTIONS ON SPOKEN CORRECTIVE FEEDBACK - Muhammad soni (Institut Pendidikan Indonesia Garut, 2018)
What the teacher applies on teaching is the representation of teacher perceptions on how the teaching process should take place. However, what the students perceive and believe would also affect to how they study at classroom. This study aimed at finding the students’ and teachers’ perceptions on spoken CF and discovering the similarities and differences of perceptions between students and teachers on spoken CF. This study was a qualitative study. Observation, interview and questionnaire were the instruments used. The two teachers involved were observed in the classroom for three meetings and also interviewed. The questionnaire was distributed to two classes representing of each teacher’s class. Both teachers and students agreed if the spoken CF is required and delayed correction is more suitable time to do. Nevertheless, both teachers and students have different arguments about the frequency of spoken CF. The discrepancy perceptions are also discovered in the priority corrected errors and the strategy of spoken CF. In sum, teachers should take into account students’ perceptions as factors to enhance the learning activities. Besides, the amount of spoken CF should also consider students’ beliefs, learning objectives, and learning activities